Study of Policy Innovation Strategy to Accelerate Achievement of Indonesian Soybean Self-sufficiency in 2035 - Hulu, Artinus; Sri Rahayu, Amy Yayuk (Pelopor Publikasi Akademika, 2024)
The high consumption and demand for soybeans without an increase in production has forced the Indonesian government always to import soybeans. Import policy must be given special attention to suppress price increases and make the rate of MSMEs continue to grow well. It's important to formulate policy designs to accelerate the fulfilment of domestic soybean supply in Indonesia. Method research uses a qualitative method with a literature review from many literature and data sources, which is then used to make a policy-making model based on incremental theory. The results indicate that self-sufficiency in soybeans may be realized if long-term arrangements are made for several things, namely expanding the area, subsidising soybean prices, import regulations and setting fair soybean import tariffs, developing the soybean jabalsim subsystem with innovation, controlling the rate of population, and the improvisation with technology innovation. Steps to recommend policies by setting import tariffs using an open and closed system following domestic production conditions, forming small analysis teams that observe, assist and work directly on the sub-section of the soybean issue, synergy and harmony of legal products within the central government-related to excise tariffs imports according to WTO standards and rigid subsidised pricing below import prices. BULOG must regulate the trade system with digital public service innovations based on the E-Agriculture Government. In addition, the government needs to partner with the private sector to increase domestic production, provide social health insurance protection and crop insurance to soybean farmers and assist with implementing smart farming agriculture.